Nutritional status of older patients with oropharyngeal dysphagia in a chronic versus an acute clinical situation. Issue 4 (August 2017) - Carrión, Silvia; Roca, Maria; Costa, Alicia; Arreola, Viridiana; Ortega, Omar; Palomera, Elisabet; Serra-Prat, Mateu; Cabré, Mateu; Clavé, Pere
Summary: Background: Oropharyngeal dysphagia (OD) is a prevalent risk factor for malnutrition (MN) in older patients and both conditions are related to poor outcome. Objective: To explore the nutritional status in older patients with OD in a chronic and an acute clinical situation. Design: We examined 95 older (≥70 years) patients with OD associated to chronic neurological diseases or aging, and 23 older patients with OD and acute community-acquired pneumonia (CAP) with videofluoroscopy; and 15 older people without OD. We collected nutritional status, measured with the Mini Nutritional Assessment (MNA ® ), anthropometric measurements, and biochemistry and bioimpedance for body composition. Functional status was assessed with the Barthel index. Results: 1) Taking into consideration patients with OD with chronic conditions, 51.1% presented a MNA ® ≤23.5; 16.7%, sarcopenia and a) reduced visceral and muscular protein compartments and fat compartment; b) muscular weakness c) intracellular water depletion, and d) reduced body weight. Patients with OD and MNA ® ≤23 needed higher levels of nectar viscosity for a safe swallow and had increased oropharyngeal residue at spoon-thick viscosity. 2) Patients with OD and CAP, 69.5%, presented an MNA ® ≤23.5 and 29.4% sarcopenia, the inflammatory response of the pneumonia adding to the more severe depletion in visceral protein and muscular mass. Conclusions: Prevalence of impaired nutritional status (malnutrition risk, and sarcopenia) among older patients with OD associated with either chronic or acute conditions is very high. In patients with OD and chronic diseases, poor nutritional status further impairs OD with an increase in oropharyngeal residue at spoon-thick viscosity. In the acute setting there is inflammation and an additional protein deficiency. These findings will help develop specific products both for OD and nutritional status in each specific clinical situation.